Double Helix of Phyllotaxis: Analysis of the Geometric Model of Plant Morphogenesis - BRIT Press (Journal of the Botanical Research Institute of Texas, 2021)
Boris Rozin. 2020. Double Helix of Phyllotaxis: Analysis of the Geometric Model of Plant Morphogenesis. (ISBN-13: 978-1-62734-748-8, pbk). Brown Walker Press/Universal Publishers, Inc., 200 Spectrum Center Drive #300, Irvine, California 92618-5004, U.S.A. (Orders: www.BrownWalkerPress.com). $39.95 US, 186 pp., color figures throughout, appendices, references, index, 6" × 9".